IL-17A inhibits airway reactivity induced by respiratory syncytial virus infection during allergic airway inflammation. Issue 8 (19th February 2013) - Newcomb, Dawn Catherine; Boswell, Madison G; Reiss, Sara; Zhou, Weisong; Goleniewska, Kasia; Toki, Shinji; Harintho, Melissa T; Lukacs, Nicholas W; Kolls, Jay K; Peebles, R Stokes
Abstract : Background: Viral infections are the most frequent cause of asthma exacerbations and are linked to increased airway reactivity (AR) and inflammation. Mice infected with respiratory syncytial virus (RSV) during ovalbumin (OVA)-induced allergic airway inflammation (OVA/RSV) had increased AR compared with OVA or RSV mice alone. Furthermore, interleukin 17A (IL-17A) was only increased in OVA/RSV mice. Objective: To determine whether IL-17A increases AR and inflammation in the OVA/RSV model. Methods: Wild-type (WT) BALB/c and IL-17A knockout (KO) mice underwent mock, RSV, OVA or OVA/RSV protocols. Lungs, bronchoalveolar lavage (BAL) fluid and/or mediastinal lymph nodes (MLNs) were harvested after infection. Cytokine expression was determined by ELISA in the lungs or BAL fluid. MLNs were restimulated with either OVA (323–229) peptide or RSV M2 (127–135) peptide and IL-17A protein expression was analysed. AR was determined by methacholine challenge. Results: RSV increased IL-17A protein expression by OVA-specific T cells 6 days after infection. OVA/RSV mice had decreased interferon-β protein expression compared with RSV mice. OVA/RSV mice had increased IL-23p19 mRNA expression in lung homogenates compared with mock, OVA or RSV mice. Unexpectedly, IL-17A KO OVA/RSV mice had increased AR compared with WT OVA/RSV mice. Furthermore, IL-17A KO OVA/RSV mice had increased eosinophils, lymphocytes and IL-13 protein expression in BAL fluid compared with WT OVA/RSV mice. Conclusions: IL-17A negatively regulated AR and airway inflammation in OVA/RSV mice. This finding is important because IL-17A has been identified as a potential therapeutic target in asthma, and inhibiting IL-17A in the setting of virally-induced asthma exacerbations may have adverse consequences.